Scale effects in tribological properties of solid-lubricating composites made of ultra-high molecular weight polyethylene filled with calcium stearate particles; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Lurie S. A.; Volkov-Bogorodskiy D. B.; Knyazeva A. G. Anna Georgievna; Panin S. V. Sergey Viktorovich; Kornienko L. A. (Numerical Simulation of Applied Problems, 2016)
Title screen